Association between high and low ambient temperature and out-of-hospital cardiac arrest with cardiac etiology in Japan: a case-crossover study - Shin Yamazaki; Takehiro Michikawa (Komiyama Printing Co. Ltd, 2017)
Abstract Objective The objective of the study was to examine the association between high and low temperature and out-of-hospital cardiac arrest (OHCA) with cardiac etiology. Methods The study was conducted under a case-crossover design. Subjects were 97,500 patients aged 40 years or older with OHCA having a cardiac etiology in Tokyo, Osaka, and Fukuoka Prefecture from 2005 to 2012. We used national data with an Utstein-style resuscitation registration. Temperature was categorized into five categories with cut points of 5, 10, 24, and 30 °C. The reference category was 10-23.9 °C. Conditional logistic regression was used with adjustment for daily means of relative humidity, atmospheric pressure, and wind speed and daily amount of precipitation and hours of daylight. Results Exposure to high temperature (≥30 °C) increased the risk of OHCA (OR = 1.11, 95% confidence interval (CI) 1.04-1.18). Further, low temperature (<5 °C) and relatively low temperature (5-9.9 °C) were also associated with OHCA (OR = 1.20, 95% CI 1.16-1.25; OR = 1.10, 95% CI 1.07-1.13, respectively). The temperature-OHCA association curves were U-shaped or J-shaped, and the association was more prominent among those aged 80 years or older. Conclusion This study shows that the occurrence of OHCA with cardiac etiology is associated with low temperature. In addition, the occurrence is also associated with high temperature in those aged 80 years or older.